กลยุทธ์การตลาดดิจิทัลเพื่อการยกระดับการท่องเที่ยวโดยชุมชนในประเทศไทย - วชิรวรกุลชัย วรวุฒิ; รัศมีโชติ บุญสม; นาครอด สุริมาศ; พูลสวัสดิ์ กิตติพร; สิทธิธนานุโชติ สมภพ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This article examines the application of digital marketing strategies to enhance Community-Based Tourism (CBT) in Thailand, focusing on tourist behavior shifts in the post-pandemic period. Through a review of relevant literature and empirical studies, the analysis highlights the role of digital technologies in strengthening communication, value perception, and tourist engagement with local communities. The findings indicate that digital marketing reduces information barriers, enhances identity presentation, and improves destination awareness. Key strategies include identity-based digital storytelling, the use of micro-influencers and user-generated content, systematic management of digital channels such as social media and search optimization, and the adoption of data-driven insights for communication and tourism management. The proposed “4D Strategic Framework”-Digital Literacy, Digital Content, Digital Collaboration, and Data-Driven Planning-illustrates how digital marketing contributes to sustainable and adaptive CBT development.